Disseminated acanthamoebiasis in a horse - Gonzalez, Maria F.; Fresneda, Karina C.; Carvallo, Francisco R. (Brazilian Journal of Veterinary Pathology, 2020)
Amoebic infections have been described in humans and animals, causing lesions in specific organs or as systemic infections. In both animals and humans, immunocompromised patients are predisposed to the infection. The present report described the macroscopic and histologic findings in a Quarter horse filly who presented with a systemic infection caused by Acanthamoeba spp. that was characterized by multinodular lesions in lung, kidney, heart, submandibular lymph node, and lip. Histopathology revealed dense inflammatory infiltrates composed of neutrophils, histiocytes, occasional multinucleated giant cells, and numerous intralesional trophozoites. Immunohistochemistry was positive for Acanthamoeba spp trophozoites in lungs, kidneys, heart, submandibular lymph node, and lip. No predisposing conditions were identified.